APPLICATION OF MAGNETIC SUSCEPTIBILITY MEASUREMENTS IN PALEOGEOGRAPHIC INVESTIGATIONS - Bol'shakov V.A. (My University, 2002)
A series of publications, in which the magnetic susceptibility measurements are used for paleoclimatic interpretations and geological correlation of the loess formation, is analyzed. As is shown, the magnetic susceptibility parameters are of a limited value for the indicated purpose, and their interpretation should be specially substantiated in each concrete case.